PROYEKSI JANGKA PANJANG PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DI KABUPATEN PARIGI MOUTONG MENGGUNAKAN LOGIKA FUZZY - Allo, Yerry; Ana, Amriana (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
One major factor to support rural development is the availability of electrical energy. Given the geographical condition of Indonesia which consists of the islands are small and many are isolated, an estimated 6,200 villages would not be possible or very difficult in electric stream by way of the expansion of the grid. Therefore we need a technology solution that can exploit or overcome the limitations of the energy sources. One of the alternatives that can be done is the utilization of solar energy using solar cell or photovoltaic sensors in the form of solar panels. Based on population growth, and the current economic growth, the Government seeks to procure solar power plants each year to facilitate villages that have not received a solar power plant. It is necessary for forecasting solar power plant needs long-term so that the procurement of solar power plants will be optimized. The forecasting is done by projecting using fuzzy logic. From the analysis of the estimated total demand for solar power in the district of Parigi Moutong using fuzzy logic can be seen as follows; needs of solar power plants by 2016 is 1090 units, the need for solar power plants in 2017 is 1220 units, the need for solar power plants in 2018 is 1350 units, the need for solar power plants in 2019 is 1470 and the need for solar power plants in 2020 is 1580 units. Keyword: Projections, Forecasting, Solar power plant, Fuzzy Logic method.